2017
DOI: 10.1073/pnas.1714175114
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 mediates a disease-associated microglial response in Alzheimer’s disease

Abstract: Dysfunction of microglia is known to play an important role in Alzheimer's disease (AD). Here, we investigated the role of RIPK1 in microglia mediating the pathogenesis of AD. RIPK1 is highly expressed by microglial cells in human AD brains. Using the amyloid precursor protein (APP)/presenilin 1 (PS1) transgenic mouse model, we found that inhibition of RIPK1, using both pharmacological and genetic means, reduced amyloid burden, the levels of inflammatory cytokines, and memory deficits. Furthermore, inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
342
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(351 citation statements)
references
References 72 publications
6
342
0
3
Order By: Relevance
“…Several studies supported this hypothesis, by showing that the pharmacological and genetic RIPK1 inhibition results in the reduction of inflammatory mediators and amyloid burden, and improved memory function (Figure ). Moreover, these studies approved the role of microglia in promoting the degradation of Aβ in vitro …”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
“…Several studies supported this hypothesis, by showing that the pharmacological and genetic RIPK1 inhibition results in the reduction of inflammatory mediators and amyloid burden, and improved memory function (Figure ). Moreover, these studies approved the role of microglia in promoting the degradation of Aβ in vitro …”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
“…Aging is known to be associated with an increase in neuroinflammation, which is mediated by microglia (Conde and Streit, 2006; Perry et al, 1993). The kinase activity of RIPK1 plays a central role in mediating neuroinflammation by promoting the activation of microglia in multiple neurodegenerative diseases including ALS, AD and multiple sclerosis (MS) (Caccamo et al, 2017; Ito et al, 2016; Ofengeim et al, 2015; Ofengeim et al, 2017). RIPK1 is suppressed by inhibitory phosphorylations mediated directly by TAK1 and by the kinases activated by TAK1, including MK2 and IKKs (Dondelinger et al, 2015; Geng et al, 2017; Jaco et al, 2017; Menon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This regulated necrosis is mediated by the activation of RIPK1 and subsequent activation of RIPK3 which in turn phosphorylates MLKL (Weinlich et al, 2017). Although necroptosis has been implicated in mediating the pathology of neurodegenerative diseases including ALS, AD and MS (Ito et al, 2016; Ofengeim et al, 2015; Ofengeim et al, 2017), a corresponding role for RDA in mediating these diseases has yet to be demonstrated. Furthermore, the molecular mechanisms of age-dependent activation of RIPK1 contributing to neurodegeneration in the human central nervous system (CNS) remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the inhibitors of RIPK1, such as Necrostatin‐1, display efficacy against multiple diseases, including Alzheimer's disease, immune‐dependent hepatitis, and glaucoma (Do, Sul, Jang, Kang, & Kim, 2017; Le Cann, Delehouzé, Leverrier‐Penna, Filliol, & Comte, 2017; Ofengeim, Mazzitelli, Ito, DeWitt, & Mifflin, 2017). In particular, the administration of RIPK1 inhibitors significantly decreases amyloid burden and cognitive defects among transgenic mice, suggesting its potential for future clinical development (Ofengeim et al., 2017). …”
Section: Necrosis: Autophagy‐related Cell Death That Contributes To Tmentioning
confidence: 99%